2020
DOI: 10.1139/cjc-2019-0268
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physical characterization, and antifungal and antibacterial activities of oleic acid capped nanomagnetite and cobalt-doped nanomagnetite

Abstract: Nanoparticles, 10–14 nm, consisting of either Fe3O4 or Co0.2Fe2.8O4 stabilized with oleic acid, were prepared using solution combustion. Their structural and magnetic properties were examined using X-ray diffractometry, scanning electron microscopy, vibrating sample magnetometry, and Fourier-transform infrared spectroscopy. The properties of both sets of materials are similar, except that the cobalt-doped particles are considerably less magnetic. The in vitro inhibitory activities of the nanoparticles were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…aureus). ,,, Doping activity of ZDI at the lowest concentration was comparatively higher than any other doped-IONPs . Apart from ZOI, minimum inhibitory concentration (MIC) was performed to determine the lowest concentration which can inhibit the growth. ,,, Studies of NDI and ZDI have shown higher MIC with the lowest amount on E. coli, B. subtilis , S. typhi , K. pneumonia , while MDI has shown no significant inhibition of E.…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%
See 4 more Smart Citations
“…aureus). ,,, Doping activity of ZDI at the lowest concentration was comparatively higher than any other doped-IONPs . Apart from ZOI, minimum inhibitory concentration (MIC) was performed to determine the lowest concentration which can inhibit the growth. ,,, Studies of NDI and ZDI have shown higher MIC with the lowest amount on E. coli, B. subtilis , S. typhi , K. pneumonia , while MDI has shown no significant inhibition of E.…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%
“…Doped-IONPs are composed of modified iron oxides by introducing foreign metals or elements into their structure. ,,, Introduction of foreign metals, also known as dopants, into an empty crystal lattice alters the physicochemical, biological, electrical, as well as optical properties of the nanoparticles . Doped-IONPs can be synthesized by coprecipitation (CP), green combustion (GC), sol–gel process (SGP), chemical polymerization approach (CPA), microwave-assisted process (MAP), hydrothermal approach (HDA). ,,,,, Multiple types of dopants, e.g.…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%
See 3 more Smart Citations